SYSTEMATIZATION OF ECONOMYKO-TECHNOLOGICAL STATIONS OF PASSENGER CARS IN OPERATION (Transport systems and technologies, 2022)
The efficiency of passenger transportation by rail depends on the level of technical condition of the passenger rolling stock. The repair and maintenance system is also important.The authors analyzed the technological states of a passenger car can during operation. It is shown that the time spent in these states and the set of technological operations that are performed at the same time do not fully reflect the relationship between the resources consumed for their implementation, the operating costs of these resources and the results.The article presents the results of systematization of the technological states of passenger cars. At the same time, the procedure for accounting for operating costs for the main types of economic activity of Ukrainian railway transport was used. A system of technical and economic indicators is proposed. It characterizes the availability and efficiency of the use of operating costs for the operation and maintenance of passenger cars in a technically sound condition. The concept of "economic and technological state of a passenger car" is substantiated.The systematization made it possible to combine, on a scientific basis, the technological and economic aspects of the operation and maintenance of passenger cars in a technically sound condition in the conditions of JSC "Ukrzaliznytsia". This will improve the system of indicators for the technical and economic evaluation of the effectiveness of the use of existing passenger cars. The proposed system will be used to justify options for updating the fleet of passenger cars through the acquisition of new models or the modernization of existing ones, taking into account the cost of the life cycle.
Keywords: passenger car, operation, technical maintenance, scheduled repairs, life cycle, maintenance.